Characterization and functional analysis of clpB gene from Acidovorax avenae subsp. avenae RS-1 - Zhang, Y.; Zhang, F.; Li, B.; Yang, Y.Z.; Ibrahim, M.; Fang, Y.S.; Qiu, W.; Masum, M. M. I.; Oliva, R. (Wiley, 2017)
The type VI secretion system (T6SS) has been reported to be highly associated with various cellular activities in strain RS‐1 of Acidovorax avenae subsp. avenae (Aaa), the pathogen of bacterial brown stripe of rice. However, the role of the clpB gene that presents in the T6SS gene cluster in Aaa pathogenicity has not been clarified. The aim of the current study was to characterize the function of clpB and to investigate its contribution to bacterial pathogenesis using insertional deletion mutation and complementation approaches. The results indicated that mutation of clpB significantly affected bacterial growth, virulence, exopolysaccharide (EPS) production, biofilm formation and expression of 13 other T6SS genes of Aaa RS‐1. The reduction of virulence may be also partially due to the change in EPS composition, which was characterized by the Fourier transform infrared (FTIR) spectra. Furthermore, analysis of protein homology modelling showed that the structure of ClpB is different from those of the other T6SS components. In addition, structural difference was observed between ClpB and Type IV pili (TFP) as well as Type IV pilus biogenesis proteins (PilP), whose functions are similar to ClpB. Taken together, this study demonstrated that the clpB gene plays a key role in Aaa bacterial virulence.